Transformation of E-Government's Impact on Transparency in Public Services: A Systematic Review and Bibliometric Analysis - Hardinda Hardinda; Muhammad Rais Rahmat Razak; Herman Lawelai; Achmad Nurmandi; Imron Sohsan (Journal Public Policy, 2026)
This study aims to analyze the transformative role of e-government in enhancing transparency in public service delivery in the era of digitization. A systematic literature review was conducted using the Scopus database from 2004 to 2024. Trend analysis and visualization techniques with RStudio software were applied to identify dominant research themes, influential authors, and leading institutions in the e-government and public service literature. The findings demonstrate that e-government substantially contributes to improving efficiency, accessibility, and transparency of public services by integrating digital technologies. Nevertheless, persistent challenges, including the digital divide and data security risks, continue to constrain effective implementation of e-government systems. Theoretically, this study highlights the need to integrate technological advances with social and economic dimensions to strengthen inclusive and sustainable public services. From a practical perspective, the research provides actionable insights for governments and policymakers in designing e-government strategies that are responsive to societal needs and technological innovations. Despite its contributions, this study is limited by including the limited scope of the literature reviewed and the retrospective nature of the analysis, which may limit relevance to future developments. Future research should incorporate broader data sources and examine emerging digital innovations to enhance the effectiveness of e-government initiatives.